Identification of Immunoglobulin E-Binding Proteins of the Xerophilic Fungus Aspergillus penicillioides Crude Mycelial Mat Extract and Serological Reactivity Assessment in Subjects with Different Allergen Reactivity Profiles - González De León, Joenice; González Méndez, Ricardo; Cadilla, Carmen L; Rivera-Mariani, Félix E; Bolaños-Rosero, Benjamín (International archives of allergy and immunology, 2018)
Aspergillus penicillioides is a very common indoor xerophilic fungus and potential causative agent of respiratory conditions. Although people are constantly exposed to A. penicillioides, no proteins with allergenic potential have been described. Therefore, we aim to confirm allergic sensitization to A. penicillioides through reactivity in serological assays and detect immunoglobulin E (IgE)-binding proteins. In an indirect ELISA, we compared the serological reactivity to A. penicillioides between subjects with specific IgE (sIgE) (group 1, n = 54) and no sIgE reactivity (group 2, n = 15) against commercial allergens. Correlations and principal component analysis were performed to identify associations between reactivity to commercial allergens and A. penicillioides. IgE-binding proteins in A. penicillioides were visualized using Western blotting (WB) in group 1. The IgE-binding proteins with the highest reactivity were analyzed by mass spectrometry and confirmed by transcript matching. There was no statistical significance (p = 0.1656) between the study groups in serological reactivity. Correlations between reactivity to A. penicillioides, dog epithelia, Aspergillus fumigatus, and Penicillium chrysogenum were observed. WB experiments showed 6 IgE-binding proteins with molecular weights ranging from 45 to 145 kDa. Proteins of 108, 83, and 56 kDa showed higher reactivity. Mass spectrometry analysis of these 3 proteins led to the putative identification of NADP-specific glutamate dehydrogenase and catalase B. This was confirmed with transcriptome analysis. These results provide evidence of the presence of potential allergenic components in A. penicillioides. Further analysis of the putatively identified proteins should reveal their allergenic potential.